Pengembangan Tong Berhitung Dalam Meningkatkan Pemahaman Konsep Materi Penjumlahan Dan Pengurangan - Maula, Dwi Inayatul; Zuliana, Eka; Kuryanto, Mohammad Syaffruddin (WASIS : Jurnal Ilmiah Pendidikan, 2025)
The purpose of this study is to find out the results of the validity, effectiveness, and practicality test of the results of the development of Tong Counting learning media on the addition and subtraction material of grade II elementary school students. This development research uses the R&D (Research and Development) method with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The data analysis in this study uses quantitative analysis and qualitative analysis. The data analysis technique in this study uses quantitative descriptive analysis techniques. The results of the validity test by 2 validators in the media aspect obtained a score of 94.32% included in the "Very Good" qualification. The results of the validity test by 2 validators on the material aspect were obtained a score of 84.38% included in the "Very Good" qualification. The results of the effectiveness test of Tong Bercounting learning media in the pretest and posttest using the Paired Sample T-Test obtained a significance value of 0.000 < 0.05. The results of the effectiveness test in the pretest and posttest using N-Gain were known that the mean N-Gain score of 0.6370 was included in the moderate criteria. The mean N-Gain percent, which is 63.6963%, is included in the criteria that are quite effective. The results of the practicality test obtained a score of 87.5%, which is included in the "Very Practical" qualification. The Tong Counting media is suitable, practical, and effective for use in elementary school students' mathematics learning.